2002
DOI: 10.1002/prot.10178
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the YciO protein from Escherichia coli

Abstract: Introduction. The YciO protein of Escherichia coli is a member of a family of proteins that also includes YrdC, HypF in E. coli, YwlC in Bacillus subtilis, and Sua5 in Saccharomyces cerevisiae (PF01300 family in PFAM database 1). Sequences similar to YciO are found either as (a) independent proteins, (b) with C-terminal extensions, or (c) as domains in larger proteins (PFAM). The proteins YwlC from B. subtilis and Sua5 from S. cerevisiae are examples of the second category. Sua5 has been identified as having a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…For several more proteins, such as HI0065 (YjeE, COG0802), HI0315 (YebC, COG0217), HI0656 (YciO, COG0009), and HI0719 (YjgF, COG0251), the exact functions remain unknown even though the crystal structures have been resolved in structural genomics studies (28,62) and the predicted biochemical functions have been listed in the database (57). Our observation that these proteins are detected either under both growth conditions (HI0719) or predominantly during microaerobic growth (HI0065, HI0315, HI0656) might eventually help in pinpointing their functions.…”
Section: Conserved Hypothetical Proteinsmentioning
confidence: 99%
“…For several more proteins, such as HI0065 (YjeE, COG0802), HI0315 (YebC, COG0217), HI0656 (YciO, COG0009), and HI0719 (YjgF, COG0251), the exact functions remain unknown even though the crystal structures have been resolved in structural genomics studies (28,62) and the predicted biochemical functions have been listed in the database (57). Our observation that these proteins are detected either under both growth conditions (HI0719) or predominantly during microaerobic growth (HI0065, HI0315, HI0656) might eventually help in pinpointing their functions.…”
Section: Conserved Hypothetical Proteinsmentioning
confidence: 99%
“…E. coli YrdC contains a novel fold with a heavily twisted central β‐sheet, which forms a basic concave surface that may preferentially bind double‐stranded RNAs 43. This fold is shared by YciO 45. The structure of S. tokodaii Sua5 revealed that the N‐terminal YrdC domain contains an E. coli ‐derived AMP molecule, and its ATP hydrolysis activity in the presence of Mg 2+ was confirmed 44.…”
Section: Introductionmentioning
confidence: 98%
“…The crystal structures of two Escherichia coli COG0009 family members YrdC and YciO (2,3) reveal an α/β twisted open-sheet structure with a positively charged cleft in its center that was proposed to form a nucleic-acid-binding site (2). Binding to double-stranded RNA (including tRNA) was experimentally verified for the E. coli YrdC protein (YrdC Ec ) (2).…”
Section: Introductionmentioning
confidence: 99%